Globus Pallidus Internus Deep Brain Stimulation Using Frame-Based vs. Frameless Stereotaxy in Dystonia: A Single-Center Experience - Eleopra, Roberto; Rinaldo, Sara; Devigili, Grazia; Mondani, Massimo; D'Auria, Stanislao; Golfrè Andreasi, Nico; Skrap, Miran; Lettieri, Christian (Frontiers in Neurology, 2021)
Objective: bilateral Globus Pallidus internus Deep Brain Stimulation (GPi-DBS) is an established and effective therapy for primary refractory dystonia. However, the comparison of frameless versus frame-based DBS surgery technique is still controversial. The aim of this retrospective study is to compare the clinical outcome of two GPi-DBS surgical techniques for patients affected by primary generalized or multi-segmental dystonia. Methods: for leads stereotaxic placement, ten patients underwent frame-based surgery and other ten subjects DBS-surgery with a frameless technique. Clinical features were evaluated at baseline, 6 and 12 months after surgery by means of the Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS). Results: frame-based GPi-DBS and frameless stereotaxic group revealed a comparable clinical outcome with no surgical complications. Conclusions: frameless technique is safe and well tolerated by patients and showed similar effectiveness of the frame-based stereotaxic surgery during GPi-DBS for primary dystonia. Notably, it could be a valid alternative solution because of the great advantage in improving the patient’s discomfort during awake surgery.